ALPHA-ADDUCIN POLYMORPHISM'S INFLUENCE ON ISCHEMIC STROKES. (June 2018) - Casanova, P.; Merlino, L.; Giacalone, G.; Zagato, L.; Sessa, M.; Comi, G.; Carpini, S. Delli; Messaggio, E.; Manunta, P.; Simonini, M.
Abstract : Objective: rs4961 Gly460Trp variant of the alpha adducin gene (ADD1) has been associated with renal sodium retention and salt sensitive hypertension. Previous studies indicated that carriers of the 460Trp allele have a higher risk of hypertension and cardiovascular (CV) diseases compared to wild-type homozygotes (Gly460Gly). The aim of this study is to assess whether there is a correlation between this ADD1 variant and the development of ischemic strokes in an Italian population. Design and method: 212 patients with ischemic stroke (IS) were recruited from the Stroke Unit of San Raffaele Hospital in Milan and divided into four categories according to Oxford Classification. These patients were compared to a cohort of elder general population (EGP, 128 patients) and a cohort of hypertensive patients (HYP, 2404 patients), both with no history of strokes. All patients analysed were genotyped for adducin family (ADD1, ADD2, ADD3) and other hypertension-related genes. Scientific data: in IS group mean age at strokes' diagnosis was 72.34 ± 11.9, 61% men, 39% women. The incidence of CV risk factors was: hypertension 66%, diabetes 22%, hypercholesterolemia 40% and hypertriglyceridemia 13%, previous stroke 14%. Mean creatinine value was 1.07 ± 0.66 mg/dL. Two comparable populations were selected with similar age (71.28 ± 6.9 years for EGP) and with the same incidence of risk factors (for HYP population). Notably, the presence of subjects homozygous for ADD1 mutated allele (rs4961 TrpTrp) is more than double in patients bearing ischemic stroke than in the two other (6.1% IS vs. 2.3% EP, p = 0.049; 6.1% IS vs. 2.2 HYP, p = 0.009; fig. 1). There was no statistically difference among the various types of stroke. No other significant associations were identified with other gene variations. Results: These data suggest a correlation between mutated alpha-Adducin and the increased incidence of all types of ischemic stroke. No correlation was found with the other hypertension-related genes analysed. Conclusions: rs4961 alpha-Adducin polymorphism should be considered as an independent risk factor for ischemic strokes. Furthermore, ischemic stroke does not appear directly linked to hypertension. Finally, alpha-Adducin polymorphism itself might be a candidate gene in the pathogenesis of stroke. Figure. No caption available.